Факторы "Сhildfree" - Ляшенко, Наталья Александровна (Національний технічний університет "Харківський політехнічний інститут", 2018)
В статье приведены результаты теоретического исследования факторов макроуровня, которые способствовали распространению добровольных отказов от рождения ребенка и в целом снижению уровня рождаемости, а именно охарактеризовано влияние технологических, экономических, политических, культурно-бытовых, социально-статусных, функционально-групповых и эстетических факторов. Оценено их влияние в зависимости от уровня образования населения и его материального обеспечения. Выявлены типовые группы причин, на которые указывают люди, которые не хотят иметь детей, поясняя свое отношение к ним. Отдельно охарактеризованы особенности отказа от рождения детей у мужчин и женщин. Во время исследования репродуктивных установок современных украинских студентов автор выявил группу респондентов, которые заявили про нежелание в будущем иметь детей вообще и обосновывали свое решение. Приведены результаты интервью с ними и было выявлено, что наиболее значимыми причинами являются нежелание утратить личный комфорт, свободное время и связать себя обязанностью заботы о ребенке. Второе место заняли страхи материальных трудностей, возникающих с появлением ребенка и необходимостью удовлетворять все его потребности. Третье место заняли проблемы при реализации собственных карьерных притязаний, которые может вызвать появление ребенка.

The article represents the results of a theoretical study of macro level factors that contributed to the proliferation of voluntary renunciation of the birth of a child and, in general, the reduction of the birth rate, which characterizes the influence of the different factors. Technological factor -reliable methods of contraception gave possibility to prevent the conception and birth of children without depriving themselves of sexual activity. Economic factor - material well-being of parents was directly dependent on the number of children; children become a "costly, unprofitable project"; no stability of work, uncertain ability to continuously provide material wealth contribute into rejection of birth. Political factor -the birth of children is not a duty to society or relatives, but becomes the personal matter of each, a conscious choice. Cultural factors - children are always the responsibility and restriction of parent’s freedom, which are considered as undesirable. Social factor - children require a lot of time and effort from their parents so they can be considered as an obstacle in career advancement and professional growth. Functional factors group -responsibility for the provision and upbringing of the child lies primarily with the marriage partners, whose union has now become unsustainable. Aesthetic factors - changed attitude to the humans body, its beauty as one of the most important capital so the women fear of the pregnancy and childbirth. Factors influence is evaluated depending on the level of education of the population and its material security. Typical groups of factors identified by people who do not want to have children are revealed, explaining their attitude to them. The peculiarities of the abandonment of the child's birth in men and women are described separately. While investigating the reproductive practices among the Ukrainian students, the author revealed a group of respondents who said they were unwilling to have children at all in the future, and substantiated this decision. The results of interviews with them were given and it was found that the most important reasons were the reluctance to lose comfort, free time, and to bind their care about the child. The second place was taken by fears of material complexities that arise with the advent of the child and the need to satisfy all its needs. The third place was taken by obstacles in the implementation of their own career aspirations, which can cause the appearance of the child.
Childfree factors
Keywords: репродуктивные установки; "чайлдфри"; причины отказа от рождения ребенка; факторы снижения рождаемости; reproductive devices; childfree; reasons of abandonment of a child; factors of birth rate decrease